Perancangan Sistem Informasi Penjualan Timbangan Berbasis Web Pada PT. Altraman - Siregar, Y. Rainhard; Pakpahan, Sorang (MEANS (Media Informasi Analisa dan Sistem), 2017)
The development of the internet world is highly expected for the present because more and more private companies, agencies take part in enlarging these developments in carrying out their business activities. So to support this, PT. Altraman is a company engaged in the sale of digital scales that offer quality products at competitive prices and provide convenience for stake holders. In this final project, an information system for the sale of web-based scales was designed at PT. Altraman which aims to process the data of stock procurement, sales and shipping and to market the scales products well through the built website media, so that it can facilitate the sale of products, and can increase sales volume. With the existence of this system it is expected that it will be easier, both for companies and customers in carrying out the sales and purchase process.